Political extremism in democracies : combating intolerance - Downs, William M. 1966- (Palgrave Macmillan, 2012)
"Political Extremism in Democracies: Combating Intolerance is a theoretically inspired, empirically rich study of political parties that have been branded as untouchable pariahs. Democracy's painful paradox seems to require tolerance of the intolerant, but democracy's defenders instead often ostracize and repress illiberal parties even when they enjoy broad electoral support. Drawing evidence from systematic comparison of contemporary pariah parties in seven European countries, the book classifies strategic responses of mainstream political actors and advances a framework for understanding cross-national differences. An inescapable, if normatively controversial, finding is that quarantining or banning extremists is less successful at containing or rolling back perceived threat than some forms of regulated inclusion"--